2011
DOI: 10.1007/s00248-011-9819-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Rhizosphere Bacterium Azospirillum brasilense Reveals an Extensive Auxin Response

Abstract: The rhizosphere bacterium Azospirillum brasilense produces the auxin indole-3-acetic acid (IAA) through the indole-3-pyruvate pathway. As we previously demonstrated that transcription of the indole-3-pyruvate decarboxylase (ipdC) gene is positively regulated by IAA, produced by A. brasilense itself or added exogenously, we performed a microarray analysis to study the overall effects of IAA on the transcriptome of A. brasilense. The transcriptomes of A. brasilense wild-type and the ipdC knockout mutant, both cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…Bacterial effector proteins are injected into host cells via type III secretion systems to facilitate pathogenicity (19). Altogether, these studies show that IAA acts as a signaling molecule for a variety of different bacterial genes that play a role in both beneficial and deleterious plant-microbe interactions (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial effector proteins are injected into host cells via type III secretion systems to facilitate pathogenicity (19). Altogether, these studies show that IAA acts as a signaling molecule for a variety of different bacterial genes that play a role in both beneficial and deleterious plant-microbe interactions (16).…”
mentioning
confidence: 99%
“…In Azospirillum brasilense Sp245, interfering with IAA biosynthesis affects the expression of ribosomal proteins, which are involved in protein synthesis. IAA also affects aerobic denitrification and adaptation to an anaerobic metabolism, cell respiration, and carbohydrate uptake (16). In the phytopathogen Agrobacterium tumefaciens C58, exogenous IAA leads to the upregulation of genes involved in amino acid synthesis and carbon metabolism (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Boscari et al ( 2013 ) showed the transcriptomic profi les during nodule development in M. truncatula-S. meliloti symbiosis and how the expression pattern is modulated by NO. In a similar manner, Van Puyvelde et al ( 2011 ) studied the transcriptomic response of A. brasilense wt and Faj009 to exogenous and endogenous auxin. They found evidence of a putative connection between the IAA and NO biosynthetic pathways since the Nap operon was up-regulated in the ipdC − mutant.…”
Section: Genetic Approachmentioning
confidence: 99%
“…Azospirillum brasilense also shows an extensive transcriptional response to auxin indole-3-acetic acid (IAA), a phytohormone produced both by that bacterium and the plant. Since many various genes such as those from secretion systems are involved in this response, it suggests that IAA acts as a signalling molecule in the planteAzospirillum interaction (Van Puyvelde et al, 2011).…”
Section: General Effectsmentioning
confidence: 99%